Jakość informacji sprawozdawczej a projekt międzynarodowego standardu rachunkowości dla małych i średnich przedsiębiorstw - Kaczmarczyk, Angelika (Credibility of reporting information and framework of the international accounting standards for small and medium entities, 2008)
Economic practice very often formulates questions about legal regulation for small and medium entities. The specificity of those units causes that they do not need legal regulations, in the field of accounting and financial reporting, for big enterprises. The main purpose of this article is an attempt to answer the following question: is it valid to create separate legal regulations, in the field of accounting and financial reporting, for small and medium entities?
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1199, s. 28-35